Extraction, Purification, Bioactivities and Application of Matrix Proteins From Pearl Powder and Nacre Powder: A Review - Pei, Jingying; Wang, Yan; Zou, Xianguo; Ruan, Huajun; Tang, Changming; Liao, Jie; Si, Guangjie; Sun, Peilong (Frontiers in Bioengineering and Biotechnology, 2021)
Natural pearls are formed when sand or parasites (irritants) accidentally enter into the oyster body and form pearls under the cover of the nacre layer. Pearl powder is a powdery substance by grinding pearls into small grains, however the nacre powder is the inner layer of outer corner layer and middle prism layer. Pearl medicine in China has a history of more than 2,000 years, pearl has the effects of calming the mind, clearing the eyes, detoxifying the muscle and so on. In this paper, the researches on the extraction of pearl powder and nacre powder, the isolation and purification of matrix protein and the various biological activities (osteogenic activity, antioxidant, anti-inflammatory, anti-apoptotic, promoting the migration of fibroblasts and so on) are reviewed in detail. To provide readers with a faster understanding, the method of extraction and purification and the application of nacre powder and pearl powder are clearly presented in the form of figures and tables. In line with the concept of waste or by-product, there are more reports of nacre extract than pearl extract, due to the expensive and limited in origin of pearls. Mainly on the direct use of nacre powder and pearl powder or on the use of extracts (mainly water soluble proteins) through experiments in vivo or in vitro, and shows whether it is effective through the results of various indexes. There is no further study on substances other than extracts, and the structural analysis of extracts needs further exploration.